2010
DOI: 10.1083/jcb.201004108
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for vertebrate Hedgehog signaling: recruitment to cilia and dissociation of SuFu–Gli protein complexes

Abstract: Hedgehog signaling through the ciliary membrane protein Smoothened dissociates the Gli transcription factors from their inhibitor, Suppressor of Fused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
380
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 347 publications
(401 citation statements)
references
References 57 publications
19
380
1
1
Order By: Relevance
“…Indeed, Fbxl17 overexpression induced Sufu degradation and Gli1 release, whereas the depletion of Fbxl17 in MEFs Ptch1 −/− led to an accumulation of Sufu–Gli1 complexes (Fig 4E and Appendix Fig S1B). Since the polyubiquitylation of Sufu precedes degradation, this model is in accordance with previous findings on Sufu–Gli complex formation and dissociation (Tukachinsky et al , 2010). …”
Section: Resultssupporting
confidence: 93%
“…Indeed, Fbxl17 overexpression induced Sufu degradation and Gli1 release, whereas the depletion of Fbxl17 in MEFs Ptch1 −/− led to an accumulation of Sufu–Gli1 complexes (Fig 4E and Appendix Fig S1B). Since the polyubiquitylation of Sufu precedes degradation, this model is in accordance with previous findings on Sufu–Gli complex formation and dissociation (Tukachinsky et al , 2010). …”
Section: Resultssupporting
confidence: 93%
“…It has been shown that Sufu retains Gli in the cytoplasm and promotes its proteolysis into a truncated repressor whereas activation of Smo in primary cilia upon Hh stimulation leads to recruitment of endogenous SufuGli complexes to the cilia and causes the dissociation of Sufu-Gli complex, allowing activated Gli proteins to enter the nucleus [40][41][42]. We found that Evc and Evc2 function upstream of Sufu to promote Gli activation.…”
Section: Discussionmentioning
confidence: 74%
“…In the absence of Shh, Ptch1 normally represses the activity of Smoothened (Smo), the seven-pass transmembrane spanning receptor which is the major signaling component and switch in this pathway. The zinc-finger transcriptional factors of Glioma-associated oncogenes (Gli) family are inhibited by the cytoplasmic protein Suppressor of Fused (SuFu) (Tukachinsky et al, 2010). Conversely, in the presence of Shh binding to Ptch1, there is relief of the inhibition of Smo.…”
Section: Sonic Hedgehog Signaling: Components Routes and Mechanismmentioning
confidence: 99%